Antimicrobial Resistance Pattern of Bacterial Isolates Causing Urinary Tract Infection - Shrestha, Padma; Malla, S.; Basnyat, S.; Dumre, S.; Upadhyay, B.; Lamichhane, S. (Journal of Nepal Health Research Council, 2009)
Not uploaded.Key words: Urinary tract infection; Multidrug-resistanceDOI: 10.3126/jnhrc.v5i2.2471Journal of Nepal Health Research Council (JNHRC) Vol. 5, No.2, October 2007 49-54